A CASE OF PLASTY OF EXTENSIVE DEFECT OF THE TRACHEA BY PREFABRICATING DELTOPECTORAL FLAP - Kayumhodjaev, A.A.; Khudaybergenov, Sh.N. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Elimination of persistent and extensive defects of the anterior wall of the trachea is an urgent problem and continues to be the subject of research and discussion of thoracic surgeons, plastic surgeons and otolaryngologists. The authors have experience in treating 102 patients with this pathology and presented a case of plasty of a large tracheal defect with a fabricated skin-fascial-cartilaginous flap on a vascular pedicle. The article describes in detail the indications for the use of displaced flaps and the main stages of plastic surgery. In severe cicatricial process around the defect and impossibility of use of the Bokstein method it is recommended the use of skin and fascial flaps moved on a vascular pedicle.